2017
DOI: 10.1080/21663831.2017.1305460
|View full text |Cite
|
Sign up to set email alerts
|

Superplastic-like flow in a fine-grained equiatomic CoCrFeMnNi high-entropy alloy

Abstract: A CoCrFeMnNi high-entropy alloy (HEA) showed elongation to failure ∼ 320% at T = 1023 K and a strain rateε = 10 −4 s −1. Strain hardening and texture weakening occurred at lowε, whereas flow softening and texture strengthening were observed at highε(> 3 × 10 −2 s −1) experiments. The strain rate sensitivity (m) decreased from 0.5 to ∼ 0.25 with increasingε. Deformation with m ∼ 0.5 and deformation-enhanced grain growth at lowε indicated superplasticity associated with grain boundary sliding. The grain boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 31 publications
5
44
0
Order By: Relevance
“…The grain size of the annealed CoCrFeMnNi was 21.7 μm excluding twin boundaries [13]. Chokshi [9] reported that CoCrFeMnNi exhibited superplasticity for samples with initial grain sizes of 1.4 μm [9,15] whereas coarser grained HEA ( ∼ 12 μm) exhibited power-law creep at 850°C. The grain size of the specimens in the present study is therefore large enough to induce the dislocation creep [9,[10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The grain size of the annealed CoCrFeMnNi was 21.7 μm excluding twin boundaries [13]. Chokshi [9] reported that CoCrFeMnNi exhibited superplasticity for samples with initial grain sizes of 1.4 μm [9,15] whereas coarser grained HEA ( ∼ 12 μm) exhibited power-law creep at 850°C. The grain size of the specimens in the present study is therefore large enough to induce the dislocation creep [9,[10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The high temperature mechanical properties of HEAs were studied earlier [9][10][11][12] and some limited results are now available documenting the occurrence of superplasticity in a number of HEAs [13][14][15][16][17]. A recent brief review summarizes the major superplastic results obtained to date [18] and also includes a description of a recent report of superplastic-like flow in a CoCrFeNiMn HEA [19]. It is well established that superplasticity requires a grain size smaller than ~10 m [20] and this may be achieved most readily through the application of severe plastic deformation (SPD) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This is considered to be an effect of high configurational entropy of mixing of a large number of elements, which diminishes the free energy sufficiently to stabilize phases with simple crystal structures [1]. The emergence of HEAs has opened up the massive composition space of hyperdimensional phase diagrams with the possibility of finding alloys with novel composition and unprecedented properties [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%